A Heuristic Method for Controller Placement and Enhanced Availability between SDN Controllers - Santos, Dorabella (2020)
The problem of guaranteeing ‘five-nines’ availability between the controllers in a SDN network is addressed. We consider the problem of controller placement under delay constraints, while assuming a sub-graph of enhanced availability between the controllers. The sub-graph can be upgraded at a given cost, to achieve the desired availability requirements. To solve this problem, we propose a heuristic method to evaluate several controller node sets and the upgrade cost of the subgraph for enhanced availability. The computational results show that slightly increasing the number of controllers can lead to a significant reduction in the upgrade cost.